Is it possible to teach good health practices using social media? (Research, Society and Development, 2021)
Social media represents a powerful weapon to promote health education. The aim of the present study was to investigate how health information is discussed and disseminated by people who do not have specific academic certification but are legitimized due to their experiences. We conducted a narrative review of the literature published from 2016 to 2021 in PubMed, using the search terms “Social Media”, “Health” and “Education”, and their variations according to MeSH. Randomized controlled trials (RCTs) which evaluated the use of social media to disseminate health information content were included in the analysis. Despite the undeniable role of social media in disseminating content concerning health practices, the use of these platforms without proper scientific support or academic certification by so-called health influencers can promote questionable content. A number of studies demonstrate that content published on social media can negatively influence the health of users. Greater scientific rigor and professional training could contribute to guarantee reliability of data regarding health information shared on social media. More studies must assess the relevance of using virtual tools for sharing content aimed at improving health and scientific reliability.